The circulation of unique reassortment strains of infectious bursal disease virus in Pakistan - Altaf HUSSAIN; Tian-tian WU; Lin-jin FAN; Yu-long WANG; Farooq Khalid MUHAMMAD; Nan JIANG; Li GAO; Kai LI; Yu-long GAO; Chang-jun LIU; Hong-yu CUI; Qing PAN; et al. (Journal of Integrative Agriculture)
Infectious bursal disease (IBD), caused by IBD virus (IBDV), is one of the most devastating and immunosuppressive diseases of the poultry and has been a constraint on the sustainable poultry production around the globe including Pakistan. While the disease is threatening the poultry industry, the nature of predominant strains of IBDV in Pakistan remained ill-defined. In this study, an epidemiology survey was conducted in the main chicken-farming regions of Pakistan. The batch of Pakistan IBDVs genes simultaneously covering both VP1 and VP2 were amplified, sequenced, and analyzed. The unique segment-reassortant IBDVs (vv-A/Uniq-B), carrying segment A from vvIBDV and segment B from one unique ancestor, were identified as one important type of circulating strains in Pakistan. The data also discovered the characteristic molecular features of Pakistan IBDVs, which will contribute to scientific vaccine selection and effective prevention of the disease.